Flame-retardant antistatic polyurethane composite material, preparation and application of flame-retardant antistatic polyurethane composite material in preparation of coal mine air door

The flame-retardant and anti-static polyurethane composite material prepared through bio-based phosphorus-containing polyol and continuous fiber reinforcement technology solves the corrosion and weight problems of coal mine dampers, and realizes a lightweight, corrosion-resistant and anti-static high-efficiency coal mine dampers, which are suitable for underground use of coal mines.

CN120248584APending Publication Date: 2025-07-04CHONGQING COPOLYFORCE NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510558113.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing coal mine dampers are prone to corrosion and have large overall weight due to metal skins, which lead to difficulties in transportation and installation, high labor intensity for workers, and traditional flame retardants are prone to precipitation and affecting material stability.

Method used

The flame-retardant and antistatic polyurethane composite material is prepared by using bio-based phosphorus-containing polyols and continuous fiber reinforcement technology. The essential flame-retardant material is formed through chemical bonding, combined with glass fiber reinforcement, and lightweight damper skeletons are made and manufactured using a specific process.

Benefits of technology

It achieves efficient flame retardant, lightweight, corrosion-resistant and anti-static properties, reduces the weight of the damper, improves the mechanical properties and safety of the materials, meets environmental protection requirements, and is suitable for complex underground environments of coal mines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248584A_ABST
    Figure CN120248584A_ABST
Patent Text Reader

Abstract

The invention discloses a flame-retardant antistatic polyurethane composite material and preparation and application of the flame-retardant antistatic polyurethane composite material to preparation of a coal mine air door, the composite material is composed of 20-30% by mass of polyurethane resin and 70-80% by mass of glass fiber, the polyurethane resin comprises a component A and a component B. The component A is diphenylmethane diisocyanate, the component B is diphenylmethane diisocyanate, and the component C is diphenylmethane diisocyanate. The component B is a polyol mixed solution formed by mixing polyester polyol, bio-based phosphorus-containing polyol, a flame retardant and an antistatic agent according to a set proportion. The preparation method comprises the steps of fiber traction, resin mixing, mold heating curing and cutting forming. The air door is prepared from the flame-retardant antistatic polyurethane composite material, so that replacement and weight reduction of a steel air door can be realized, transportation and installation of the air door are facilitated, the labor intensity of workers is reduced, and intelligent transformation is facilitated; and the cable has good flame-retardant, antistatic and corrosion-resistant properties, and is more suitable for complex environments in underground coal mines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coal mine air doors, and specifically relates to a flame-retardant and antistatic polyurethane composite material, a preparation method thereof, and an application in making coal mine air doors. Background Art

[0002] Coal mine air doors play a crucial role in the mine ventilation system. It is a key device for regulating the air flow and air pressure underground, and has an irreplaceable role in maintaining the stable operation of the ventilation system, ensuring fresh air circulation underground, and effectively preventing the accumulation of gas and dust. By precisely controlling the ventilation volume, the air door can also promote the temperature balance underground, improving the production efficiency and the quality of the working environment. Most of the existing coal mine air doors use a welded metal profile skeleton, and then use a polymer material or iron sheet as the skin. Among them, the iron sheet is easily corroded, and using only the polymer material as the skin cannot effectively reduce the weight of the air door. This results in that the coal mine air door can only be transported and installed by manpower in the narrow roadway. Due to its large weight, the labor intensity of workers is high, and the risk coefficient of transportation and installation is high. Summary of the Invention

[0003] In view of this, the present invention provides a flame-retardant and antistatic polyurethane composite material, its preparation and application in making coal mine air doors. By introducing a bio-based phosphorus-containing polyol, combining continuous fiber reinforcement technology and a specific preparation process, a flame-retardant and antistatic polyurethane composite material is prepared, and further made into a coal mine air door, so as to solve the problems of serious corrosion and large weight of the existing air doors.

[0004] To achieve the above invention object, the specific technical solution of the present invention is as follows:

[0005] A flame-retardant and antistatic polyurethane composite material, by mass fraction, the composite material is composed of 20%-30% of polyurethane resin and 70%-80% of glass fiber. The polyurethane resin includes components A and B. Among them, component A is diphenylmethane diisocyanate, and component B is a polyol mixture obtained by mixing polyester polyol, bio-based phosphorus-containing polyol, flame retardant, and antistatic agent in a set ratio;

[0006] The bio-based phosphorus-containing polyol has the structural formula I: Among them, R1 to R11 contain 2 to 4 compounds with the structural formula II, and the rest are The structural formula II is

[0007] Preferably, the mass ratio of polyester polyol, bio-based phosphorus-containing polyol, flame retardant, and antistatic agent in component B is 45:14.6:20.4:20.

[0008] Preferably, the flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, phosphate esters, melamine and its derivatives, brominated epoxy resin, and decabromodiphenylethane additive flame retardants, and the antistatic agent is a mixture composed of one or more of 1,3-dimethylimidazolium tetrafluoroborate, N-octylpyridinium bromide, N-butyl-N-methylpiperidinium bromide, N-butyl-N-methylpyrrolidinium bromide, tributylmethylammonium chloride, N-ethyl, methylmorpholinium bromide, and tributylethylphosphonium bromide ionic liquids.

[0009] According to the different surface resistances achieved, the dosage of the antistatic agent is different. For example, when the surface resistance reaches 10 9 Ω, the polyol mixture: antistatic agent is 72:28; when the surface resistance reaches 10 8 Ω, the polyol mixture: antistatic agent is 65:35; when the surface resistance < 10 8 Ω, carbon fiber is used on the surface.

[0010] Preferably, the preparation method of the bio-based phosphorus-containing polyol is as follows:

[0011] (1) According to a molar ratio of 1:8 to 10, add phytic acid with a mass fraction of 10 - 20% and ammonia water with a concentration of 5% - 10% into the reaction kettle in sequence. After adding water to dissolve, heat to 40 - 50 °C, and carry out condensation reflux reaction for 20 - 200 min. After purification and drying, the intermediate of structural formula III is obtained. The structural formula III is where R 13 ~R 24 contains 2 - 4 H⁺, and the rest are

[0012] (2) Add the compound of structural formula II into a flask equipped with a condensation device, and then add an organic solvent according to a volume ratio of 1:3 - 5, heat to 30 °C - 100 °C to dissolve. At 25 °C - 150 °C, add the intermediate of structural formula III. The molar ratio of the compound of structural formula II to the intermediate of structural formula III is 2 - 4:1. After reacting for 1 h - 10 h, remove the solvent, and dry to obtain the bio-based phosphorus-containing polyol.

[0013] In the described flame-retardant and antistatic polyurethane composite material, in step (2) of the preparation method of the bio-based phosphorus-containing polyol, the organic solvent is any one or several of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, chlorobenzene, dichlorobenzene, trichlorobenzene, ethylene glycol methyl ether, ethylene glycol ethyl ether, or 1,4-dioxane.

[0014] Preferably, the glass fiber is ECT glass fiber.

[0015] A preparation method of a flame-retardant and antistatic polyurethane composite material includes the following steps:

[0016] Step 1: The traction fibers pass through the oven and the yarn dividing plate and are drawn into the mold, and the traction felt / cloth is drawn into the mold.

[0017] Step 2: Take the bio-based phosphorus-containing polyol, mix it with the flame retardant and the antistatic agent in proportion, and add components A and B to the two-component resin mixer.

[0018] Step 3: Turn on the mold heating device to fully heat the mold.

[0019] Step 4: Turn on the oven and start the traction device.

[0020] Step 5: Turn on the glue injector and the cutting machine.

[0021] Step 6: The resin and glass fiber are cured through the mold to obtain a flame-retardant and antistatic bio-based phosphorus-containing intumescent flame-retardant polyurethane profile, and it is cut to a fixed length by the cutting machine to obtain a composite material, and the composite material can be a skeleton profile or a plate.

[0022] Preferably, in Step 1, the fiber traction speed is 0.2 - 2 m / min. In Step 3, the mold is divided into three sections, so that the mold temperature at the front section of the mold near the yarn inlet is 150°C - 170°C, the middle section is 170°C - 190°C, and the rear section near the outlet of the tubular profile is 190°C - 210°C. In Step 4, the oven temperature is set at 60°C - 150°C. In Step 5, the injection pressure is set at 0.5 - 1 MPa.

[0023] An application of using a flame-retardant and antistatic polyurethane composite material to make a coal mine air door includes the following steps:

[0024] Step 1: Process two kinds of skeleton profiles and plates to the required sizes, and injection mold the skeleton connectors 1 and 2.

[0025] Step 2: Connect the skeleton profile 1 with the skeleton connector 1, and connect the skeleton profile 2, the skeleton profile 1 and the skeleton profile 2 with the skeleton connector 2 to form an air door skeleton and a pedestrian door skeleton, and use the plate as the skin.

[0026] Step 3: Assemble the air door skeleton, the pedestrian door skeleton and the skin by means of gluing and mechanical connection, and assemble reinforcing steel plates at the four corners, connecting rods, hinges and cylinders.

[0027] Step 4: Build the air door frame into the wall, and then assemble the air door to the frame through the hinge; assemble the pedestrian door to the air door through the hinge.

[0028] Step 5: Assemble the connecting rod and the cylinder to the air door.

[0029] Step 6: Assemble the air pipe and the air door cylinder controller, and then the coal mine air door is made.

[0030] A bio - based phosphorus - containing intrinsically flame - retardant polyurethane air door for coal mines of the present invention has significant beneficial effects compared with the prior art, which are mainly reflected in the following aspects:

[0031] 1. High - efficiency intrinsic flame retardancy and no precipitation of flame retardants: The present invention uses bio - based phosphorus - containing polyols. By directly incorporating bio - based DOPO derivatives into the polyurethane molecular chain, an intrinsically flame - retardant and antistatic polyurethane composite material is formed. When this material burns, it can self - crosslink and expand to form a dense carbon layer, and crosslink with the pyrolysis small molecules of the polymer to generate a carbon layer with high thermal stability, effectively isolating oxygen and heat and inhibiting flame propagation. At the same time, at high temperatures, the phosphorus - containing polyols crosslink with the pyrolysis small molecules of the polyurethane to generate a carbon layer with high thermal stability, further enhancing the flame - retardant effect. The flame - retardant performance can reach UL94 V - 0 level and meet the MT113 standard. Compared with traditional additive flame retardants, the intrinsically flame - retardant design eliminates the problem of flame retardant precipitation, significantly improves the flame - retardant efficiency, and ensures the long - term stability of the material's flame - retardant performance; at the same time, it reduces the dosage of additive flame retardants and improves the mechanical properties of the flame - retardant polyurethane composite material.

[0032] 2. Excellent mechanical properties: Through continuous glass fiber reinforcement technology and chemical bonding between bio - based phosphorus - containing polyols and polyurethane resin, reducing the dosage of additive flame retardants, the idler central shaft of the present invention has excellent mechanical properties. Tests show that the tensile strength of the composite material prepared by the pultrusion process is ≥1200MPa, and the flexural strength is ≥1200MPa. The introduction of DOPO derivatives reduces or eliminates the use of additive flame retardants, which not only enhances the rigidity of the molecular chain but also improves the overall strength of the composite material. The tensile strength and flexural strength of this composite material are about 2 - 3 times that of the steel central shaft, capable of withstanding greater loads and impacts, and effectively extending the service life of the idler.

[0033] 3. Lightweight design: The density of the polyurethane composite material is only about one - quarter of that of steel, and the tensile strength and flexural strength are about twice that of steel, realizing the lightweight design of the air door. This not only reduces the overall weight of the air door, lowers the transportation and installation costs, but also facilitates the intelligent transformation of the air door.

[0034] 4. Excellent corrosion resistance: The idler central shaft can resist the erosion of various corrosive media such as acids, alkalis, and salts, and its corrosion resistance is better than that of metal idlers, especially suitable for the complex and harsh environment in coal mine shafts. Its excellent corrosion resistance effectively extends the service life of the idler and reduces the maintenance cost.

[0035] 5. Excellent antistatic performance: The synergistic effect of bio - based phosphorus - containing polyols and antistatic agents can make the surface resistivity of the idler central shaft ≤3×10 8Ω, compliant with MT113 standard, can effectively prevent static electricity accumulation and reduce the fire risk caused by static sparks. This characteristic significantly improves the safety of the idler in the complex environment of coal mines.

[0036] 6. Environmental protection and sustainability: The bio-based binary hydroxyl-terminated DOPO derivative flame retardant of the present invention adopts a halogen-free and environmentally friendly design. The synthetic monomers (such as phytic acid) have a wide range of sources and are renewable, reducing the carbon footprint in the production process and the dependence on non-renewable resources. Compared with traditional halogen-containing flame retardants, the present invention avoids the generation of toxic gases during combustion, meets the requirements of green manufacturing and sustainable development, and has significant environmental friendliness.

[0037] 7. High production efficiency: Using a large amount of additive flame retardants to achieve a good flame retardant effect will affect the curing time and quality of polyurethane, resulting in a slow pultrusion speed (below 0.25 m / min). Since the bio-based phosphorus-containing polyol used in the present invention participates in the reaction of polyurethane and belongs to inherent flame retardancy, it has no impact on the reaction of polyurethane, has a fast pultrusion speed, and high production efficiency.

[0038] Other advantages, objectives and features of the present invention will be described to some extent in the subsequent specification, and to some extent, will be obvious to those skilled in the art based on the study of the following text, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in detail preferably with reference to the accompanying drawings, where:

[0040] Figure 1 is the forming process diagram of the air door frame / skin;

[0041] Figure 2 is the assembly diagram of the non-metallic air door;

[0042] Figure 3 is the assembly diagram of the non-metallic air door frame;

[0043] Figure 4 Physical diagram of the non-metallic air door. DETAILED DESCRIPTION OF THE INVENTION

[0044] The following describes the embodiments of the present invention through specific examples. Those skilled in the art can easily understand the other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the drawings provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner. Without conflict, the following embodiments and the features in the embodiments can be combined with each other.

[0045] Among them, the drawings are only for illustrative purposes, showing only schematic diagrams, not physical diagrams, and should not be construed as a limitation to the present invention; in order to better illustrate the embodiments of the present invention, some components in the drawings will be omitted, enlarged or reduced, which does not represent the size of the actual product; for those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0046] In the drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components; in the description of the present invention, it should be understood that if there are terms such as "upper", "lower", "left", "right", "front", "rear", etc. indicating the orientation or positional relationship, they are based on the orientation or positional relationship shown in the drawings. It is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the positional relationship in the drawings are only for illustrative purposes and should not be construed as a limitation to the present invention. For those of ordinary skill in the art, the specific meanings of the above terms can be understood according to specific circumstances.

[0047] Please refer to Figures 1 to 4 , Figure 1 , which is a process diagram for the forming of the air door frame / skin. A bio-based phosphorus-containing inherently flame-retardant polyurethane air door for coal mines. The material of the air door is a continuous fiber-reinforced flame-retardant and antistatic polyurethane composite material. The composite material is composed of 20%-30% of polyurethane resin and 70%-80% of glass fiber. The polyurethane resin includes components A and B. Among them, component A is diphenylmethane diisocyanate, and component B is a polyol mixture obtained by mixing polyester polyol, bio-based phosphorus-containing polyol, flame retardant, and antistatic agent in a set ratio.

[0048] Among them, component A is diphenylmethane diisocyanate. 4,4'-MDI, modified MDI, polymeric MDI (PMDI), etc. that can be used for pultrusion can be selected. For the polyester polyol in component B, adipic acid-based polyester polyol, phthalic anhydride (PA)-based polyester polyol, or hydrolysis-resistant polyester polyol, etc., which are polyols for pultrusion, can be selected.

[0049] The mixing ratio of the flame retardant and the bio-based phosphorus-containing polyol is determined according to the flame retardancy level requirements. For example, to achieve a V0 flame retardancy level, the mass ratio of the polyester polyol to the bio-based phosphorus-containing polyol is 72:28; to meet the MT113 flame retardancy requirements, the mass ratio of the polyester polyol to the bio-based phosphorus-containing polyol is 63:37.

[0050] Preparation of bio-based phosphorus-containing polyol:

[0051] (1) According to a molar ratio of 1:8, 15% by mass of phytic acid and 8% ammonia water are successively added to a reaction kettle. After adding water for dissolution, it is heated to 0 °C, and the condensation reflux reaction is carried out for 100 min. After purification and drying, an intermediate of structural formula III is obtained. The structural formula III is where R 13 ~R 24 contains H+ with a number of 2, and the rest are

[0052] (2) The compound of structural formula II is added to a flask equipped with a condensation device, and then an organic solvent is added according to a volume ratio of 1:3 and heated to 80 °C for dissolution. At 80 °C, the intermediate of structural formula III is added. The molar ratio of the compound of structural formula II to the intermediate of structural formula III is 3:1. After reacting for 7 h, the solvent is removed, and after drying, the bio-based phosphorus-containing polyol can be obtained.

[0053] In the following examples, component A used is 4,4'-MDI, the polyester polyol in component B is adipic acid-based polyester polyol, the flame retardant is aluminum hydroxide, and the antistatic agent is 1,3-dimethylimidazolium tetrafluoroborate.

[0054] A preparation method of a flame retardant and antistatic polyurethane composite material includes the following steps:

[0055] Step 1: The traction fiber passes through an oven and a yarn dividing plate and is drawn into a mold, and the traction felt / cloth enters the mold.

[0056] Step 2: Take the bio-based phosphorus-containing polyol, mix it with the flame retardant and the antistatic agent in proportion, and add components A and B to a two-component resin mixer.

[0057] Step 3: Turn on the mold heating device to fully heat the mold.

[0058] Step 4: Turn on the oven and start the traction device.

[0059] Step 5: Turn on the injection molding machine and the cutting machine.

[0060] Step 6: The resin and glass fiber are cured through the mold to obtain a flame retardant and antistatic bio-based phosphorus-containing inherently flame retardant polyurethane profile, and it is cut to a fixed length by a cutting machine to obtain a composite material. The composite material can be a skeleton profile or a plate.

[0061] Prepare the skeleton profiles and sheets for air dampers according to the above process method and the formula of the following examples:

[0062] Example 1 (basic formula)

[0063] Formula: Polyol 24.2 phr, bio-based phosphorus-containing polyol 15.4 phr, antistatic agent 15.4 phr; MDI: 45 phr; Glass fiber: 80 wt%.

[0064] Process: Pultrusion speed 0.5 m / min, die temperature at the front stage 160 °C, middle stage 180 °C, and rear stage 190 °C, injection pressure 0.8 MPa.

[0065] Example 2 (high flame-retardant formula)

[0066] Formula: Polyol 14.6 phr, bio-based phosphorus-containing polyol 20.4 phr, antistatic agent 20 phr; MDI: 45 phr; Glass fiber: 80 wt%.

[0067] Process: Pultrusion speed 0.5 m / min, die temperature at the front stage 160 °C, middle stage 180 °C, and rear stage 190 °C, injection pressure 0.8 MPa.

[0068] Example 3

[0069] Formula: Polyol 16.6 phr, bio-based phosphorus-containing polyol 13 phr, additive flame retardant 10 phr, antistatic agent 15.4 phr; MDI: 45 phr; Glass fiber: 80 wt%.

[0070] Process: Pultrusion speed 0.5 m / min, die temperature at the front stage 160 °C, middle stage 180 °C, and rear stage 190 °C, injection pressure 0.8 MPa.

[0071] Example 4

[0072] Formula: Polyol 34.6 phr, bio-based phosphorus-containing polyol 20.4 phr, antistatic agent surface carbon fiber; MDI: 45 phr; Glass fiber: 80 wt%.

[0073] Process: Pultrusion speed 0.5 m / min, die temperature at the front stage 160 °C, middle stage 180 °C, and rear stage 190 °C, injection pressure 0.8 MPa.

[0074] Comparative Example 1

[0075] Formula: Polyol 55 phr, MDI: 45 phr; Glass fiber: 80 wt%.

[0076] Process: Pultrusion speed is 0.5 m / min, die temperature at the front section is 160 °C, middle section is 180 °C, and rear section is 190 °C, and injection pressure is 0.8 MPa.

[0077] Comparative Example 2

[0078] Formulation: Polyol 14.6 phr, additive flame retardant 25 phr, antistatic agent 15.4 phr; MDI: 45 phr; Glass fiber: 80 wt%.

[0079] Process: Pultrusion speed is 0.5 m / min, die temperature at the front section is 160 °C, middle section is 180 °C, and rear section is 190 °C, and injection pressure is 0.8 MPa.

[0080] Perform performance tests on the materials prepared in Examples 1 - 6 to obtain the test results shown in Table 1

[0081] Table 1 Test Results

[0082]

[0083]

[0084] It can be reflected from the above table that due to the participation of bio - based phosphorus - containing polyol in the reaction, this characteristic can not only ensure that the composite material prepared without adding an additive flame retardant can achieve a flame - retardant effect (flame retardancy can reach MT113), but also maintain the mechanical properties of the composite material. At the same time, when adding a large amount of other additives (such as an antistatic agent, making the surface resistance ≤ 3×10 8 Ω), the mechanical properties of the composite material only decrease slightly, as shown in Example 2; reducing the dosage of bio - based phosphorus - containing polyol and antistatic agent can prepare composite materials with different flame - retardant and antistatic specifications. For example, in Example 1, the flame - retardant performance of the composite material reaches V0, the surface resistance reaches 3.8×10 9 Ω, and the mechanical properties are excellent; due to the high price of bio - based phosphorus - containing polyol, using a method of mixing bio - based phosphorus - containing polyol with an additive flame retardant or completely using an additive flame retardant to prepare the composite material to reduce costs will reduce the mechanical properties of the composite material, such as in Example 3 and Comparative Example 2; to further reduce the surface resistance of the composite material profile, using carbon fiber on the surface of the composite material can make the surface resistance ≤ 10 3 Ω, and the mechanical properties are almost the same as those of non - flame - retardant and antistatic composite materials, as shown in Example 4.

[0085] The application of using the flame - retardant and antistatic polyurethane composite material to make a coal mine air door includes the following steps:

[0086] Step 1: Process two kinds of skeleton profiles and plates to the required sizes, and injection - mold to prepare skeleton connectors 1 and 2;

[0087] Step 2: Connect the skeleton profiles 1 using the skeleton connectors 1. Connect the skeleton profiles 2, 1, and 2 using the skeleton connectors 2 to form the air door skeleton and the pedestrian door skeleton, and use the plates as the skins.

[0088] Step 3: Assemble the air door skeleton, the pedestrian door skeleton, and the skins by means of gluing and mechanical connection, and assemble the reinforcing steel plates at the four corners, connecting rods, hinges, and cylinders.

[0089] Step 4: Build the air door frame into the wall, and then assemble the air door to the frame through hinges; assemble the pedestrian door to the air door through hinges.

[0090] Step 5: Assemble the connecting rods and cylinders to the air door.

[0091] Step 6: Assemble the air pipes and the air door cylinder controller, and then the coal mine air door is made.

[0092] Figure 2 It is the assembly drawing of the non-metallic air door; Figure 3 It is the assembly drawing of the non-metallic air door skeleton; Figure 4 The physical drawing of the non-metallic air door.

[0093] The following uses specific specific examples to illustrate the implementation manners of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific implementation manners. The details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the diagrams provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner. Without conflict, the following embodiments and the features in the embodiments can be combined with each other.

Claims

1. A flame-retardant and antistatic polyurethane composite material, characterized in that, By mass fraction, the composite material is composed of 20%-30% polyurethane resin and 70%-80% glass fiber. The polyurethane resin includes components A and B. Component A is diphenylmethane diisocyanate, and component B is a polyol mixture obtained by mixing polyester polyol, bio-based phosphorus-containing polyol, flame retardant, and antistatic agent in a set ratio; The bio-based phosphorus-containing polyol is of structural formula Ⅰ: Among R1 to R11, there are 2 to 4 compounds of structural formula Ⅱ, and the rest are The structural formula Ⅱ is 2. The flame-retardant and antistatic polyurethane composite material according to claim 1, wherein In component B, the mass ratio of polyester polyol, bio-based phosphorus-containing polyol, flame retardant, and antistatic agent is 45:14.6:20.4:

20.

3. The flame-retardant and antistatic polyurethane composite material according to claim 1, wherein The flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, phosphate esters, melamine and its derivatives, brominated epoxy resin, and decabromodiphenylethane additive flame retardants. The antistatic agent is a mixture composed of one or more of 1,3-dimethylimidazolium tetrafluoroborate, N-octylpyridinium bromide, N-butyl-N-methylpiperidinium bromide, N-butyl-N-methylpyrrolidinium bromide, tributylmethylammonium chloride, N-ethyl, methylmorpholinium bromide, and tributylethylphosphonium bromide ionic liquids.

4. The flame-retardant and antistatic polyurethane composite material according to claim 1, wherein The preparation method of the bio-based phosphorus-containing polyol is as follows: (1) According to a molar ratio of 1:8 to 10, add phytic acid with a mass fraction of 10 - 20% and ammonia water with a concentration of 5% - 10% into the reaction kettle in sequence. After adding water for dissolution, heat to 40 - 50 °C, carry out condensation reflux reaction for 20 - 200 min, and obtain the intermediate of structural formula III after purification and drying. The structural formula III is wherein R 13 ~R 24 contains H⁺ with a number of 2 - 4, and the rest are (2) Add the compound of structural formula II into a flask equipped with a condensing device, and then add an organic solvent according to a volume ratio of 1:3-5 and heat it to 30°C to 100°C for dissolution. At 25°C to 150°C, add the intermediate of structural formula III. The molar ratio of the compound of structural formula II to the intermediate of structural formula III is 2-4:

1. After reacting for 1h to 10h, remove the solvent and dry it to obtain the bio-based phosphorus-containing polyol.

5. The flame-retardant and antistatic polyurethane composite material according to claim 4, wherein In step (2), the organic solvent is any one or several of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, chlorobenzene, dichlorobenzene, trichlorobenzene, ethylene glycol methyl ether, ethylene glycol ethyl ether, or 1,4-dioxane.

6. The flame-retardant and antistatic polyurethane composite material according to claim 1, wherein The glass fiber is ECT glass fiber.

7. A preparation method of a flame-retardant and antistatic polyurethane composite material, characterized in that, It includes the following steps: Step 1: The traction fiber passes through an oven and a yarn splitting board and is pulled into a mold, and the traction felt / cloth enters the mold. Step 2: Take the bio-based phosphorus-containing polyol, mix it with the flame retardant and the antistatic agent in proportion, and add components A and B to a two-component resin mixer. Step 3: Turn on the mold heating device to fully heat the mold. Step 4: Turn on the oven and start the traction device. Step 5: Turn on the injection molding machine and the cutting machine. Step 6: The resin and glass fiber are cured through the mold to obtain a flame-retardant and antistatic bio-based phosphorus-containing inherently flame-retardant polyurethane profile, which is cut to a fixed length by the cutting machine to obtain a composite material. The composite material can be a skeleton profile or a plate.

8. The preparation method of a flame-retardant and antistatic polyurethane composite material according to claim 7, wherein, In step 1, the fiber traction speed is 0.2-2m / min. In step 3, the mold is divided into three sections, so that the temperature of the front section of the mold near the yarn inlet is 150°C-170°C, the middle section is 170°C-190°C, and the rear section near the outlet of the tubular profile is 190°C-210°C. In step 4, the oven temperature is set to 60°C-150°C. In step 5, the injection pressure is set to 0.5-1MPa.

9. An application of making a coal mine air door with a flame-retardant and antistatic polyurethane composite material, characterized in that, It includes the following steps: Step 1: Process two kinds of skeleton profiles and plates to the required sizes and injection mold the skeleton connectors 1 and skeleton connectors 2; Step 2: Connect the skeleton profiles 1 using the skeleton connectors 1, and connect the skeleton profiles 2, skeleton profile 1 and skeleton profile 2 using the skeleton connectors 2 to form a damper skeleton and a pedestrian door skeleton, and use the plates as the skins; Step 3: Assemble the damper skeleton, pedestrian door skeleton and the skins by means of gluing and mechanical connection, and assemble reinforcing steel plates at the four corners, connecting rods, hinges and cylinders; Step 4: Build the damper frame into the wall, and then assemble the damper to the frame through hinges; Assemble the pedestrian door to the damper through hinges; Step 5: Assemble the connecting rods and cylinders to the damper; Step 6: Assemble the air pipes and the damper cylinder controller, thus manufacturing the coal mine damper.